2007
DOI: 10.1007/s00253-006-0647-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermentation temperature on hydrogen production from cow waste slurry by using anaerobic microflora within the slurry

Abstract: We examined hydrogen production from a dairy cow waste slurry (13.4 g of volatile solids per liter) by batch cultures in a temperature range from 37 to 85 degrees C, using microflora naturally present within the slurry. Without the addition of seed bacteria, hydrogen was produced by simply incubating the slurry, using the microflora within the slurry. Interestingly, two peaks of fermentation temperatures for hydrogen production from the slurry were observed at 60 and 75 degrees C (392 and 248 ml H2 per liter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(43 citation statements)
references
References 51 publications
0
41
0
2
Order By: Relevance
“…This variation is another important characteristic that could permit the coexistence of so close relatives. Temperature adaptability is likely the result of regulation of enzymatic activity, which might directly influence the efficiency of the biochemical pathways involved in Microcystis decomposition (Sridhar et al, 2000;Yokoyama et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation is another important characteristic that could permit the coexistence of so close relatives. Temperature adaptability is likely the result of regulation of enzymatic activity, which might directly influence the efficiency of the biochemical pathways involved in Microcystis decomposition (Sridhar et al, 2000;Yokoyama et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During the anaerobic incubation of the Microcystis slurry, Clostridium species appear to have the collaborative ability to hydrolyze initial substrates and produce low molecular weight intermediates, such as acetate and ethanol, and even directly generate biohydrogen gas (Chang et al, 2006;Yokoyama et al, 2007;Seedorf et al, 2008). The occurrence of these processes in the fermentation systems was confirmed by the presence of methanogenic Archaea (our unpublished data), which anaerobically utilize low molecular weight intermediates (for example, acetate or H 2 /CO 2 ) to produce CH 4 (Supplementary Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…However, comparatively little is known about the occurrence of anaerobic extreme thermophiles, with growth optima above 65 u C, in animal faeces. A study has reported the presence of an anaerobic extreme thermophile, Caldanaerobacter subterraneus, in cow faeces (Yokoyama et al, 2007a), implying that dormant extreme thermophiles might prevail in animal faeces. Many anaerobic thermophiles can degrade hemicellulosic material, the second most abundant component of plant fibre; however, the other extremely thermophilic hemicellulolytic bacteria were not isolated from animal faeces but from hot springs or oil-producing wells (Wagner & Wiegel, 2008).…”
mentioning
confidence: 99%
“…With the inoculum pretreatment (boiling at 100 C for 1 h) and the acclimation process (55 C for 3 d) for the seed sludge, they found that dark fermentation of acid-hydrolyzed ground wheat was more beneficial under thermophilic condition (55 C) than mesophilic condition (37 C). Actually, by the inoculation of mesophilically and thermophilically digested sludge, thermophilic acidogenic sludge, cow waste slurry, etc., peak H 2 yields can be commonly achieved under thermophilic environments (55e60 C) with other complex wastes as the substrate [34,35]. In our view, better H 2 -producing performances under thermophilic conditions can be attributed to selective enrichment of some efficient H 2 -producing thermophiles, which are capable of producing more H 2 by utilizing complex substrate components (to be illustrated in section 3.4).…”
Section: Biogas and H 2 Productionmentioning
confidence: 95%